2015
DOI: 10.18352/ijc.561
|View full text |Cite
|
Sign up to set email alerts
|

Turning conflict into collaboration in managing commons: A case of Rupa Lake Watershed, Nepal

Abstract: A collaborative effort to manage watershed commons 745Abstract: A growing body of literature on the commons has provided fascinating and intricate insights on how some local institutions have successfully managed to avoid a seemingly inevitable "tragedy of the commons" once popularized by Garrett Hardin. Primarily benefitting from the recent studies on the commonpool resources conducted by Elinor Ostrom and colleagues, polycentric selforganization and autonomy, rather than the direct state or market control ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Extending the discussion on concurrent multifunctionality to include CPRs, we found that the increased number of visitors, resulting in an increased competition over the free resource of trails in the mountain landscape, combined with increased difference in use, was perhaps the most prominent source of conflict in the study area. This is in line with other studies on conflicts over CPRs [31,59,60], where the increase of resource-users was found to result in conflicts.…”
Section: Conflicts Over Trails In a Multifunctional Landscapesupporting
confidence: 92%
See 1 more Smart Citation
“…Extending the discussion on concurrent multifunctionality to include CPRs, we found that the increased number of visitors, resulting in an increased competition over the free resource of trails in the mountain landscape, combined with increased difference in use, was perhaps the most prominent source of conflict in the study area. This is in line with other studies on conflicts over CPRs [31,59,60], where the increase of resource-users was found to result in conflicts.…”
Section: Conflicts Over Trails In a Multifunctional Landscapesupporting
confidence: 92%
“…A fruitful collaboration between actors enhances the capacity of agencies and communities to manage common resources in multifunctional landscapes [57,58]. Thus, it is strongly suggested that collaboration is an important means to handle conflicts between stakeholders [59,60]. Here, it is useful to take advantage of existing social networks to build trust and to promote social relationships [28,[60][61][62][63].…”
Section: Components Of Collaboration In Multifunctional Landscapesmentioning
confidence: 99%
“…Canada and Manitoba can learn from countries like Nepal to effectively design conservation areas and watersheds protected by community institutions and their governance mechanisms. These community-based conservation models refute the Eurocentric theory of the "tragedy of the commons" (Chaudhary et al, 2015) that still influences conservation programs in Europe and North America.…”
Section: Discussionmentioning
confidence: 96%
“…Ostrom (1990: 25) challenges the presumption that individuals cannot organize themselves and always need to be organized by external authorities. This CPR model of Ostrom has been adopted by many developing nations, and in some cases has also succeeded in preventing the problem of free-riding to some extent (Cox et al, 2010;Saunders, 2014;Chaudhary et al, 2015).…”
Section: A Critical Reflection On Cpr Theorymentioning
confidence: 99%